Characterization of different male sterile lines on morphological characters of India mustard [Brassica juncea (L.) Czern & Coss ] along with their maintainer - R. Sutar1 and B.B. Mangle1, *Prem Kumar Gautam1, R.K.S. Rathore2, A. (International Multidisciplinary Research Journal, 2011)
Male sterility in plants can be controlled by nuclear genes cytoplasm or by both. There are three types of male sterility as G.M.S, C.M.S and C.G.M.S. Science a good number of CMS lines are availed in Indian mustard now a day; it is desirable to have a complete data base for their identification at earliest possible stage of growth with morphological characterization. The present investigation to work the characterization of male sterility in five CMS systems in Indian Mustard along with their maintainers based on morphological characteristics .The CMS system taken for investigation include. Ogura, Tournefortil Oxyrrhina, Moricandia and Trachystoma . The seeds obtained for above mentioned material were sown in the R.B.S college Agricultural .research farm, Khandri Agra .A set of ten characters were observed in all the male sterile and their maintainer line. These characters include plant height, Number of primary branches and secondary branches, main shoot length, number of seeds per siliqua, Number of siliqua on main shoot, Pod length, 1000 seed weight, seed yield per plant.